2020
DOI: 10.3390/s20226612
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Autoencoder-Based Flaw Detection for Steel Wire Ropes

Abstract: Visual perception-based methods are a promising means of capturing the surface damage state of wire ropes and hence provide a potential way to monitor the condition of wire ropes. Previous methods mainly concentrated on the handcrafted feature-based flaw representation, and a classifier was constructed to realize fault recognition. However, appearances of outdoor wire ropes are seriously affected by noises like lubricating oil, dust, and light. In addition, in real applications, it is difficult to prepare a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…However, recently developed recursive canonical correlation analysis algorithm do not require a reference for accurate assessment [17]. Another approach to ND also relies on a distance metric, but this time the distance is not measured from reference points stored in memory but from a sample's reconstructed version [5,[18][19][20][21]. In the last quoted approach, the boundary is defined by a trained model.…”
Section: Novelty Detection In Condition Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recently developed recursive canonical correlation analysis algorithm do not require a reference for accurate assessment [17]. Another approach to ND also relies on a distance metric, but this time the distance is not measured from reference points stored in memory but from a sample's reconstructed version [5,[18][19][20][21]. In the last quoted approach, the boundary is defined by a trained model.…”
Section: Novelty Detection In Condition Monitoringmentioning
confidence: 99%
“…In articles [5,13,18,[22][23][24][25] novelty detection algorithms were presented for gearbox monitoring. Other applications include bearings fault detection [14,19,26,27], maintenance support system for gas turbines [10,11,28] and rope inspection [21]. The solutions presented in these articles are, however, usually at the experimental stage.…”
Section: Novelty Detection In Condition Monitoringmentioning
confidence: 99%
“…Nonetheless, the limited sample size and the reliance on hand-crafted features hampered robustness in noisy environments. This was evidenced in [24] which showed that the model accuracy drops to 80.5% when training/testing with a different dataset. Moreover, the utility of CNNs combined with image processing techniques was shown to increase the accuracy of the model in [22] from 93.3% to 95.5% [18].…”
mentioning
confidence: 93%
“…When the concentrated broken strand exceeds the scrap standard, the whole rope needs to be replaced, leading to a short life cycle. At the same time, in this short life cycle, the quantity of fracture defect data is small, which makes it difficult to use supervised learning methods to detect defects [7]. There is little literature on machine-vision-based defect detection for sealed wire ropes, but researchers have carried out a lot of work on surface defect detection for nonsealed ordinary wire ropes.…”
Section: Introductionmentioning
confidence: 99%
“…When the concentrated broken strand exceeds the scrap standard, the whole rope needs to be replaced, leading to a short life cycle. At the same time, in this short life cycle, the quantity of fracture defect data is small, which makes it difficult to use supervised learning methods to detect defects [ 7 ].…”
Section: Introductionmentioning
confidence: 99%